B0 shimming for in vivo magnetic resonance spectroscopy: Experts' consensus recommendations. (28th June 2020) - Juchem, Christoph; Cudalbu, Cristina; de Graaf, Robin A.; Gruetter, Rolf; Henning, Anke; Hetherington, Hoby P.; Boer, Vincent O.
Abstract : Magnetic resonance spectroscopy (MRS) and spectroscopic imaging (MRSI) allow the chemical analysis of physiological processes in vivo and provide powerful tools in the life sciences and for clinical diagnostics. Excellent homogeneity of the static B0 magnetic field over the object of interest is essential for achieving high‐quality spectral results and quantitative metabolic measurements. The experimental minimization of B0 variation is performed in a process called B0 shimming. In this article, we summarize the concepts of B0 field shimming using spherical harmonic shimming techniques, specific strategies for B0 homogenization and crucial factors to consider for implementation and use in both brain and body. In addition, experts' recommendations are provided for minimum requirements for B0 shim hardware and evaluation criteria for the primary outcome of adequate B0 shimming for MRS and MRSI, such as the water spectroscopic linewidth. Abstract : Magnetic resonance spectroscopy allows the chemical analysis of physiological processes in vivo. Excellent homogeneity of the static B0 magnetic field is essential for achieving high‐quality spectral results and quantitative metabolic measurements. We summarize the concepts of B0 field homogenization, strategies for B0 shimming and crucial factors to consider for implementation and use in both brain and body. Experts' consensus recommendations are provided for minimum requirements for B0 shim hardware and evaluation criteria for successful (or adequate) B0 shimming.